Local cerebral glucose utilisation in treated and untreated patients with Parkinson's disease. Issue 8 (August 1984) - Rougemont, D; Baron, J C; Collard, P; Bustany, P; Comar, D; Agid, Y
Abstract : Using the 18f-fluoro-2-deoxy-d-glucose technique and positron emission tomography (PET), the local cerebral glucose utilisation (1CMRGlc) was measured in four non-demented patients with early-onset, bilateral Parkinson's disease characterised by the predominance of akinesia. The study was done twice, first in the untreated condition, and then after levodopa had been resumed. Despite a marked clinical improvement, we found no alteration in 1CMRGlc between the first and second studies in any of the brain structure analysed. Compared to control values, 1CMRGlc in the basal ganglia was moderately increased in both studies. These essentially negative findings agree with most previous human or animal studies, and indicate that the functional alterations in the central dopaminergic systems of patients with Parkinson's disease have metabolic correlates that are too small to be demonstrated by current PET devices.